Morphological, ecological and geographical evolution of the Neotropical genus Nasa (Loasaceae subfamily Loasoideae). (9th March 2021) - Acuña-Castillo, Rafael; Romoleroux, Katya; Luebert, Federico; Henning, Tilo; Weigend, Maximilian
Abstract: The Andean uplift is recognized as one of the most important events shaping the Neotropical biota. Previous phylogenetic reconstructions of Nasa, a mostly tropical Andean genus, have been unable to address its historical biogeography or ancestral character estimations in detail due to insufficient sampling and phylogenetic resolution. The main goal of the present study is to provide an expanded and highly resolved phylogenetic reconstruction of the genus to address these questions. We were able to sequence 87 of the 125 taxa (species and subspecies) of Nasa, for the plastid markers trnL–trnF, matK, trnS–trnG and rps16 . Our results show that Nasa falls into four well-supported clades, clade I is sister to the rest of the genus and is composed of Central Andean species. The remaining three clades are more widely distributed, found also in the Amotape-Huancabamba Zone (AHZ) and the northern Andes. Our morphological analyses were able to identify plausible phylogenetic affinities of most Nasa spp. for which molecular data are unavailable, with three of the morphological clusters composed mostly by species of three well-supported clades (Clades II, III and IV). Historical biogeography indicates that Nasa has a history spanning 50 Myr, its early events predating most of the Andean uplift. Nasa appears to have originally occupied mid-elevation, seasonally dry habitats. By the mid-Miocene ( c . 15 Mya) expansion into new forest edge and undergrowth habitats took place. This coincides with renewed uplift that increased the complexity of the abiotic conditions in the Andes. The AHZ is retrieved as the most important centre of diversification since the closure of the West Andean Portal and appears to be a cradle of clades of Nasa . Conversely, the central Andes, the most likely area of origin of the genus, house mostly ancient, species-poor clades.